2021
DOI: 10.3390/toxics9020033
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Phthalate Metabolites and Markers of Endothelial Dysfunction in Adolescents and Young Adults

Abstract: Endothelial function is crucial in the pathogenesis of circulatory and cardiovascular toxicity; epidemiologic research investigating the association between phthalate exposure and endothelial dysfunction remains limited. We examined the associations between exposures to specific phthalates (di-2-ethylhexyl phthalate, DEHP; di-n-butyl phthalate, DnBP) and circulating endothelial and platelet microparticles (EMPs and PMPs) in adolescents and young adults. Of the 697 participants recruited, anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance and increased carotid intima-media thickness [12,13,44]. Thus, exposure to DEHP may mediate impaired HRV through these mechanisms.…”
Section: Discussionmentioning
confidence: 81%
“…Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance and increased carotid intima-media thickness [12,13,44]. Thus, exposure to DEHP may mediate impaired HRV through these mechanisms.…”
Section: Discussionmentioning
confidence: 81%
“…Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance, and increased carotid intima-media thickness [13,14,44]. Thus, exposure to DEHP may mediate impaired HRV through these mechanisms.…”
Section: Discussionmentioning
confidence: 81%
“…Exogenous and endogenous metabolites with its downstream oxidative stress have been recognized as the common underlying cellular mechanism for the development of endothelial dysfunction among many risk factors for atherosclerosis [ 34 , 35 ]. In this study, primary DNA damage detected in peripheral blood using alkaline comet assay could result from the oxidative stress and reactive cyto/geno-toxic metabolites in circulation.…”
Section: Discussionmentioning
confidence: 99%